2021
DOI: 10.1002/jnr.24772
|View full text |Cite
|
Sign up to set email alerts
|

Better modulation for risk decision‐making after optimized magnetic stimulation

Abstract: Decision-making, as a kind of high-level cognitive process that involves selecting response options that will ultimately maximize gains while minimizing losses, is of great significance to human survival and adaptation (Hsu et al., 2005). Adaptive decision-making is important for utilizing only relevant and valid feedback and ignoring irrelevant feedback. Individuals can capitalize on feedback to provide learning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The RMT was measured based on the stimulation intensity from the right first dorsal interosseous muscle using a handheld 70 mm figure-of-eight coil. RMT was defined as the lowest intensity required to evoked a small response (>50 mV) in more than five of ten consecutive trials in the right first dorsal interosseous muscle [36].…”
Section: Study Interventions: Mri-navigated Rtmsmentioning
confidence: 99%
“…The RMT was measured based on the stimulation intensity from the right first dorsal interosseous muscle using a handheld 70 mm figure-of-eight coil. RMT was defined as the lowest intensity required to evoked a small response (>50 mV) in more than five of ten consecutive trials in the right first dorsal interosseous muscle [36].…”
Section: Study Interventions: Mri-navigated Rtmsmentioning
confidence: 99%
“…Individual decision-making behavior holds promise as a potential therapeutic indicator for substance use disorders and may also influence cravings. Recent neuroscientific studies have revealed rTMS’s capacity to modulate human behavior and cognition, effectively intervening in individual decision-making processes [ 14 , 15 ]. When individuals make behavioral choices and decisions, they involve value assessment and self-control, in which the DLPFC is closely associated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, greater activation in the OFC in cocaine abusers compared to a control group may reflect differences in the anticipation of reward while less activation in the DLPFC and MPFC may reflect differences in planning and working memory [ 20 ]. High-frequency rTMS in the left dlPFC can enhance neuronal excitability in this region [ 15 ], thereby bolstering decision-making abilities and performance on decision-making tasks. Existing research suggests that high-frequency rTMS (HF-rTMS) over the left dlPFC may decrease cravings and impulsivity in patients with MUD, aiding them in avoiding risky decisions [ 21 , 22 ] and improving decision-making function [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive brain stimulation techniques, such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS), have been widely used to improve performance in several cognitive domains, including executive functions, memory performance, and decision-making in healthy subjects [ 1 , 2 , 3 , 4 ]. tDCS is a technique by applying weak electrical currents to the scalp to modulate the neuronal activity, and therefore change the behaviors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%